2015
DOI: 10.4236/ajps.2015.69142
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Soybean Cultivars and Seed Density

Abstract: Plant, environmental conditions and management type will determine final crop yield. Enhanced yield can be reached by using well-adapted and potentially productive genotypes; all of them ally to crop cultural practices and management. Among these, seed density stands out, once it interferes with plant morphology and competition for water and nutrients. Thus, this study aimed to evaluate the effect of varied seed densities on agronomic traits in soybean, besides identifying cultivars with wide adaptability to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 9 publications
4
22
0
6
Order By: Relevance
“…This fact was reported by SOARES et al (2015), in which sowing density influences competition for soil resources such as water and nutrients and light absorption.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…This fact was reported by SOARES et al (2015), in which sowing density influences competition for soil resources such as water and nutrients and light absorption.…”
Section: Resultssupporting
confidence: 55%
“…LIMA et al (2012) also commented that the setting of the sowing density is an important tool in the optimization of plant growth, biomass gain and grain production. SOARES et al (2015), in research conducted in Minas Gerais, confirmed that there is an interaction between the densities of sowing and soybean cultivars and showed that the population of 300 thousand plants per hectare is the most suitable for cultivation in the evaluated sites. Results obtained by LUDWIG et al (2011) also corroborate the existence of cultivars x population interaction.…”
Section: Introductionmentioning
confidence: 67%
“…The number of grain per pod and the grain harvest index were not significantly influencied by cultivars (Table 2). Soares et al (2015a) and Felisberto et al (2015) observed an effect of cultivars on the agronomic traits evaluated. The authors affirm that it was expected, since cultivars have different genetic background, growth habit, maturation group and other characteristics providing variations.…”
Section: Resultsmentioning
confidence: 94%
“…This behavior is due to a framework of these three growth habit groups: determinate, indeterminate, and semideterminate (Tian et al, 2010;Soares et al, 2015). Knowledge of these characteristics influences population distribution of the crop in the field, so the best space arrangement should enable high agricultural productivity (Board and Kahlon, 2013).…”
Section: Introductionmentioning
confidence: 99%